A mitochondrial analysis reveals distinct founder effect signatures in Canarian and Balearic goats. (7th July 2015) - Ferrando, A.; Manunza, A.; Jordana, J.; Capote, J.; Pons, A.; Pais, J.; Delgado, T.; Atoche, P.; Cabrera, B.; Martínez, A.; Landi, V.; Delgado, J. V.; et al.
Summary In the course of human migrations, domestic animals often have been translocated to islands with the aim of assuring food availability. These founder events are expected to leave a genetic footprint that may be recognised nowadays. Herewith, we have examined the mitochondrial diversity of goat populations living in the Canarian and Balearic archipelagos. Median‐joining network analysis produced very distinct network topologies for these two populations. Indeed, a majority of Canarian goats shared a single ancestral haplotype that segregated in all sampled islands, suggesting a single founder effect followed by a stepping‐stone pattern of diffusion. This haplotype also was present in samples collected from archaeological assemblies at Gran Canaria and Lanzarote, making evident its widespread distribution in ancient times. In stark contrast, goats from Majorca and Ibiza did not share any mitochondrial haplotypes, indicating the occurrence of two independent founder events. Furthermore, in Majorcan goats, we detected the segregation of the mitochondrial G haplogroup that has only been identified in goats from Egypt, Iran and Turkey. This finding suggests the translocation of Asian and/or African goats to Majorca, possibly as a consequence of the Phoenician and Carthaginian colonisations of this island.